Diagnostic Challenges in Difficult-to-Localize Insulinomas: A Case Report and Review of Literature - Nikica M. Grubor; Nikola N. Grubor; Marjan Micev (Diagnostics, 2024)
Non-somatostatin receptor expressing hypovascular insulinomas can be challenging to prove through imaging. This case highlights the utility of a structured approach to molecular imaging in patients with confirmed endogenous hyperinsulinemia. A 54-year-old woman was admitted because of a sudden loss of consciousness. Her relative reported that she complained of dizziness, intense sweating, blurry vision, and upper extremity tingling before becoming unresponsive for 20 min, after which the patient had little recollection of the event. She experienced similar episodes of shorter duration, trouble recalling everyday events, and unintentional weight gain of over 10 kg during the previous two years. Abdominal magnetic resonance imaging (MRI) and multidetector computerized tomography (MDCT) were unremarkable. Selective arterial calcium stimulation significantly increased hepatic venous insulin concentrations when the superior mesenteric and gastroduodenal arteries were stimulated. Technetium-99m (99mTc) octreotide single-photon emission computed tomography (SPECT) did not localize the lesion. Gallium-68 DOTA-Exendin-4 PET/CT acquisition was performed. A single intense 2 cm hyperperfused pancreatic lesion was located anteriorly in the head of the pancreas. Earlier targeted PET/CT imaging and recognition of significant neuropsychiatric symptoms attributable to the patient’s hypoglycemic state might have accelerated the resolution of her condition and obviated the need for unnecessary testing.